Asthma Therapies on Pulmonary Tuberculosis Pneumonia in Predominant Bronchiectasis–Asthma Combination - Yeh, Jun-Jun; Lin, Hui-Chuan; Yang, Yu-Cih; Hsu, Chung-Y.; Kao, Chia-Hung (Frontiers in Pharmacology, 2022)
Background: It is sometimes difficult to distinguish between asthma and bronchiectasis as their symptoms overlap, and these two diseases are associated with pulmonary tuberculosis (PTB) or pneumonia. Objective: The purpose of this study is to determine the effects of bronchodilator drugs, steroids, antidepressants drugs, and antianxiety drugs on the risks of PTB or pneumonia in patients with bronchiectasis–asthma combination or bronchiectasis–asthma–chronic obstructive pulmonary disease combination—BCAS cohort. Methods: After propensity score matching, we retrospectively studied patients with BCAS (N = 620) and without BCAS (N = 2,314) through an analysis. The cumulative incidence of PTB or pneumonia was analyzed through Cox proportional regression. After adjustment for sex, age, comorbidities, and medications [including long-acting beta2 agonist/muscarinic antagonists (LABAs/LAMAs), short-acting beta2 agonist/muscarinic antagonists (SABAs/SAMAs), leukotriene receptor antagonist, montelukast, steroids (inhaled corticosteroids, ICSs; oral steroids, OSs), anti-depressants (fluoxetine), and anti-anxiety drugs (benzodiazepines, BZDs)], we calculated the adjusted hazard ratios (aHR) and their 95% confidence intervals (95% CI) for these risks. Similar to OSs, ICSs are associated with an increased risk of PTB or pneumonia, lumping these two as steroids (ICSs/OSs). Results: For the aHR (95% CI), with non-LABAs/non-OSs as the reference 1, the use of LABAs [0.70 (0.52–0.94)]/OSs [0.35 (0.29–0.44)] was associated with a lower risk of PTB or pneumonia. However, the current use of LABAs [2.39 (1.31–4.34)]/SABAs [1.61 (1.31–1.96)], steroids [ICSs 3.23 (1.96–5.29)]/OSs 1.76 (1.45–2.14)], and BZDs [alprazolam 1.73 (1.08–2.75)/fludiazepam 7.48 (1.93–28.9)] was associated with these risks. The current use of LAMAs [0.52 (0.14–1.84)]/SAMAs [1.45 (0.99–2.11)] was not associated with these risks. Conclusion: The current use of LAMAs/SAMAs is relatively safe with respect to PTB or pneumonia risks, but LABAs/SABAs, steroids, and BZDs could be used after evaluation of the benefit for the BCAS cohort. However, we must take the possible protopathic bias into account.